Review of Legal Compliance of Funding Models and Pivoting Events of Indonesian Digital Start-ups - Normalita Destyarini; Darminto Hartono Paulus; Ariesta Wibisono Anditya (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
The existence of digital start-up growth in the existence of digital start-ups that are still looking for a business model so that it can be possible to make changes to the business model in the acceleration process, this affects the funding agreement made by the accelerator. So it is necessary to know the funding scheme for the establishment of digital start-ups and the impact of changing business models on investment contracts. The purpose of this paper is to determine the legal relationship of accelerators, in this case venture capital, to digital start-up in Indonesia, funding schemes and the legal consequences of changing business models by digital start-ups. The research method used is normative juridical, the research specification used is descriptive-analytical. The results showed that funding by Venture capital using convertible notes instrument, against investment contracts if digital start-ups do pivot. It is concluded from the results of the research that the implementation of funding by Ventures Capital will re-do the agreement with the assessment indikator. The implementation is carried out based on the Law of BUMN the Law of Limited Liability Company, the Law of Investment and the Venture capital Head Company Articles of Association.